Numerical simulation and experimental study on the effect of bond strength on the formability of steel/aluminum composite panels. (December 2022) - Gao, B.X.; Zou, D.K.; Guo, Y.C.; Xiao, H.
Highlights: Numerical calculations are performed with progressive failure and element accurate removal analysis. Considering the failure initiation criteria under Hashin's theory and failure evolution based on the energy criterion. Comprehensive failure analysis of composite materials. The cohesive element model (CEM) was used to simulate delamination. Abstract: A finite element model for the tension and bending of steel/aluminum/steel and aluminum/steel/aluminum three-layer symmetrical composite panels is established using the finite element simulation software ABAQUS to explore the delamination mechanism and influencing factors of the impacted composite interface. Analysis of the stress change law of each layer of the composite panels shows that during failure, necking changes the distribution of the matrix stress on both sides, the steel layer is the first to neck and fracture because it loses the restraint of the aluminum layer. Furthermore, the results reveal an interesting relationship, where the strength of the interfacial bond determines the delamination sequence of the composite plate matrix, resulting in a fracture with a cross-x or step-like morphology. The correctness of the simulation and analysis results is verified by tension and bending experiments in the laboratory.